Sustainable multi-unit process plan generation in a reconfigurable manufacturing environment: A comparative study of three hybrid-meta-heuristics - Touzout, Faycal A.; Benyoucef, Lyes (Proceedings (IEEE International Conference on Emerging Technologies and Factory Automation), 2018)
Achieving competitiveness in nowadays manufacturing market goes through being cost and time-efficient as well as being environmentally benign. In this paper, three hybrid-meta-heuristics are proposed and compared to solve the single-product multi-unit process plan generation problem. Moreover, in the quest of achieving a sustainable reconfigurable manufacturing system (RMS), three criteria are considered: respectively, the total production cost, the completion time and the greenhouse gases (GHG) emitted by the manufacturing system during the production process. To illustrate the applicability of the approaches, an example is presented and numerical results analysed.